(untitled) (American Journal of Islam and Society, 2014)
The Mennonites relationship ongoing with Iran has developed over a period of more than twenty years. This essay traces the development of our relationships with Iranians and our program with Iran, how it began with relief and reconstruction and progressed through a student exchange to an ongoing interfaith dialogue and visiting scholars. The roles of several key Iranians, to whom much credit must be given, will also be discussed. The views expressed herein concerning the development of Mennonite engagement with Iran are the personal views of the author and do not represent those of any Mennonite institution.